Power, Politics and Episcopal Authority : the Bishops of Cremona and Lincoln in the Middle Ages (1066-1340). - Silvestri, Angelo (Cambridge Scholars Publishing, 2015)
It is impossible to completely understand the history of the medieval church without understanding how bishops' control was exercised in the diocese, and in the city. This book assesses the differences, shifts and changes in the power of the bishop in the cities and the dioceses of Lincoln and Cremona from the middle of the 11th century to the mid-14th century. Lincoln, with the biggest medieval diocese in England and with its unique series of bishops such as Hugh of Wells, Hugh of Avalon, Ro ...